Nanocone-structure hydrogen evolution electrode with chromium trisulfide / nickel disulfide interface and preparation method and application of nanocone-structure hydrogen evolution electrode

By electrochemical deposition on the nickel network to form a nanocone structure catalytic coating with dichromium trisulfide/trini nickel disulfide interface, the problems of high catalyst cost and difficulty in desorption of hydrogen atoms in the existing electrolytic water hydrogen production technology are solved, and efficient hydrogen production and stable catalyst performance are achieved.

CN119640312AActive Publication Date: 2025-03-18SHANGHAI SHAANXI COAL HIGH-TECH RES INST CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411557963.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the high cost of catalysts and the difficulties of the three-nickel disulfide catalyst in desorption of hydrogen atoms limit the development and application of this technology.

Method used

A nanocone structure catalytic coating with dichromium trisulfide/trini nickel disulfide interface was grown on it by electrochemical deposition method to form a hydrogen evolution electrode with high active sites and optimized hydrogen atom desorption.

Benefits of technology

The decomposition activity of the catalyst is improved, the difficulty of desorption of hydrogen atoms is reduced, the overpotential required for decomposition of water is significantly reduced, and the hydrogen evolution efficiency is improved. The preparation method is simple and efficient, and the catalyst is strongly stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640312A_ABST
    Figure CN119640312A_ABST
Patent Text Reader

Abstract

The invention discloses a nanocone structure hydrogen evolution electrode with a chromium trisulfide / nickel disulfide interface and a preparation method of the nanocone structure hydrogen evolution electrode. The hydrogen evolution electrode comprises a conductive substrate and a nanocone structure catalytic coating with the chromium trisulfide / nickel disulfide interface, wherein the nanocone structure catalytic coating grows on the conductive substrate in situ and is provided with the chromium trisulfide / nickel disulfide interface. The nickel net is used as a conductive substrate, the nanocone structure coating with the chromium trisulfide / nickel disulfide interface is grown on the nickel net in situ to serve as a hydrogen evolution catalyst, the chromium trisulfide / nickel disulfide interface layer is high in water decomposition activity, the problem that hydrogen atoms of the nickel disulfide catalytic coating are difficult to desorb is solved, and the hydrogen evolution performance of the nickel sulfide catalytic coating is improved. Meanwhile, more active sites are introduced, so that the overpotential required by water decomposition is greatly reduced, and the hydrogen evolution efficiency is effectively improved; a one-step electrochemical deposition method is adopted, the preparation method is simple and efficient, the catalyst stability is high, and the prepared hydrogen evolution electrode has wide application prospects in the field of hydrogen production through alkaline electrolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water electrolysis hydrogen evolution electrodes, and in particular to a nano-cone structure hydrogen evolution electrode with a chromium trisulfide / nickel disulfide interface, and a preparation method and application thereof. Background Art

[0002] As energy and environmental issues become increasingly severe and energy supply and demand become increasingly tight, we urgently need to seek a new type of energy. Water electrolysis hydrogen production technology is a simple, safe, and sustainable way to produce high-purity hydrogen. It is expected to replace fossil fuels in the future sustainable energy supply in terms of extracting oxygen and hydrogen, and play an important role. However, the high cost of water electrolysis hydrogen production technology limits its development. Therefore, it is necessary to study highly catalytically active and inexpensive catalysts.

[0003] Platinum group noble metal-based materials have strong electrocatalytic effects on hydrogen evolution reaction (HER) due to their high intrinsic activity, but they are expensive and scarce, so they cannot be used on a large scale. Nickel disulfide (Ni3S2) has been widely studied in the field of HER due to its high abundance in the earth's reserves, high conductivity and excellent activity. However, during the catalytic reaction of HER in Ni3S2 catalyst, hydrogen atoms are easily adsorbed on the active s sites, which greatly improves the adsorption of hydrogen and forms a strong S-Hads bond, making it difficult to desorb Hads, thereby reducing the catalytic activity of HER. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a nano-cone structure hydrogen evolution electrode with a chromium trisulfide / nickel disulfide interface and a preparation method and application thereof. A nickel mesh is used as a conductive substrate, and a nano-cone structure coating with a chromium trisulfide / nickel disulfide interface is in-situ grown on the nickel mesh by electrochemical deposition as a hydrogen evolution catalyst. The chromium trisulfide / nickel disulfide interface layer has high water decomposition activity, which optimizes the problem of difficult desorption of hydrogen atoms from the nickel disulfide catalytic coating, while introducing more active sites, greatly reducing the overpotential required for water decomposition, and effectively improving the hydrogen evolution efficiency.

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a nanocone structure hydrogen evolution electrode with a chromium trisulfide / nickel disulfide interface, comprising a conductive substrate and a nanocone structure catalytic coating with a chromium trisulfide / nickel disulfide interface grown in situ on the conductive substrate.

[0006] The hydrogen evolution electrode of the present invention comprises a conductive substrate and a nano-cone structure catalytic coating having a chromium trisulfide / nickel disulfide interface. The conductive substrate adopts a nickel mesh. The chromium trisulfide / nickel disulfide interface in the catalytic coating has high water decomposition activity, which optimizes the problem of difficult desorption of hydrogen atoms in the nickel disulfide catalytic coating, while introducing more active sites, greatly reducing the overpotential required for water decomposition, and effectively improving the hydrogen evolution efficiency.

[0007] Furthermore, the thickness of the catalytic coating is 20-45 μm, and the size of the nanocone structure is 50-200 nm.

[0008] Furthermore, the catalytic coating comprises the following components in terms of molar percentage: 49.57%-55.38% nickel, 2.02%-4.74% chromium and 42.22%-46.72% sulfur.

[0009] The second aspect of the present invention provides a method for preparing the nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface according to the first aspect, comprising the following steps:

[0010] S1, dissolving a soluble nickel salt, a soluble chromium salt and a soluble sulfur salt in a solvent, adjusting the pH and temperature to obtain a precursor solution;

[0011] S2. Placing a conductive substrate in the precursor solution for electrochemical deposition, in situ growing a nanocone structure catalytic coating having a chromium trisulfide / nickel disulfide interface, and obtaining the nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface.

[0012] The invention adopts a one-step electrodeposition method to in-situ grow a nano-cone structure coating with a chromium trisulfide / nickel disulfide interface on the surface of a conductive substrate. The preparation method is simple and efficient, and the catalyst has strong stability.

[0013] Furthermore, in S1, the soluble nickel salt is selected from one or more of nickel sulfate, nickel chloride and nickel nitrate; the soluble chromium salt is selected from one or more of chromium sulfate, chromium chloride and chromium nitrate; and the soluble sulfur salt is selected from thiourea and / or sodium sulfide.

[0014] Furthermore, in S1, the concentration of nickel ions in the precursor solution is 1-5 mmol / L, the concentration of chromium ions is 0.5-3 mmol / L, and the concentration of sulfur ions is 10-40 mmol / L.

[0015] Furthermore, in S1, the pH of the precursor solution is 4-5, and the temperature is 80-95°C.

[0016] Furthermore, in S1, the solvent is deionized water.

[0017] Furthermore, in S2, the electrochemical deposition is performed by a standard three-electrode system, which includes a working electrode, a counter electrode and a reference electrode, wherein the conductive substrate serves as the working electrode, the platinum sheet serves as the counter electrode, and the Ag / AgCl electrode serves as the reference electrode.

[0018] Further, in S2, the current density of the electrochemical deposition is -5 to -20 mA / cm 2 , the electrochemical deposition time is 30-90min.

[0019] Furthermore, in S2, the electrochemical deposition also includes washing and drying steps.

[0020] Furthermore, before S2, the process also includes: placing the conductive substrate in anhydrous ethanol, hydrochloric acid and distilled water in turn for cleaning to remove surface oil and oxides; the conductive substrate is a nickel mesh.

[0021] The third aspect of the present invention provides the use of the nanocone structure hydrogen evolution electrode with chromium trisulfide / nickel disulfide interface described in the first aspect in catalyzing hydrogen evolution reaction in alkaline water electrolysis.

[0022] Beneficial effects of the present invention:

[0023] The present invention uses a nickel mesh as a conductive substrate, and in-situ grows a nano-cone structure coating with a chromium trisulfide / nickel disulfide interface on the nickel mesh as a hydrogen evolution catalyst, wherein the chromium trisulfide / nickel disulfide interface layer has a high water decomposition activity, optimizes the problem of difficult desorption of hydrogen atoms from the nickel disulfide catalytic coating, and introduces more active sites, greatly reduces the overpotential required for water decomposition, and effectively improves the hydrogen evolution efficiency.

[0024] The present invention adopts a one-step electrochemical deposition method, the preparation method is simple and efficient, the catalyst has strong stability, and the prepared hydrogen evolution electrode has broad application prospects in the field of hydrogen production by alkaline water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 It is a flow chart of the preparation of the nano-cone structure hydrogen evolution electrode with chromium trisulfide / nickel disulfide interface of the present invention;

[0027] Figure 2are scanning electron microscope (SEM) surface morphology images of the Cr-Ni3S2 electrode and the Ni3S2 electrode prepared in Example 1 and Comparative Example 1 of the present invention, wherein a1 and a2 are surface morphology images of the Ni3S2 electrode prepared in Comparative Example 1, and b1 and b2 are surface morphology images of the Cr-Ni3S2 electrode prepared in Example 1;

[0028] Figure 3 1 are transmission electron microscope (TEM) images of the Cr-Ni3S2 electrode and the Ni3S2 electrode prepared in Example 1 and Comparative Example 1 of the present invention, wherein a1, a2, and a3 are TEM images of the Ni3S2 electrode prepared in Comparative Example 1, and b1, b2, and b3 are TEM images of the Cr-Ni3S2 electrode prepared in Example 1;

[0029] Figure 4 X-ray diffraction patterns of the Cr-Ni3S2 electrode and the Ni3S2 electrode prepared in Example 1 of the present invention and Comparative Example 1;

[0030] Figure 5 The Raman images of the Cr-Ni3S2 electrode and the Ni3S2 electrode prepared in Example 1 and Comparative Example 1 of the present invention;

[0031] Figure 6 X-ray photoelectron spectroscopy analysis of the Cr-Ni3S2 electrode and the Ni3S2 electrode prepared in Example 1 of the present invention and Comparative Example 1;

[0032] Figure 7 The current density-potential curves of the electrodes in Examples 1-4 of the present invention tested in a three-electrode system;

[0033] Figure 8 The current density-potential curves of the electrodes in Example 1 of the present invention and Comparative Examples 1-2 tested under a three-electrode system are shown. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] This embodiment provides a nanocone structure hydrogen evolution electrode with a chromium trisulfide / nickel disulfide interface, comprising a conductive substrate and a nanocone structure catalytic coating with a chromium trisulfide / nickel disulfide interface grown in situ on the conductive substrate.

[0036] As a specific example, the thickness of the catalytic coating is 20-45 μm, and the size of the nanocone structure is 50-200 nm; in terms of molar percentage, the catalytic coating includes the following components: 49.57%-55.38% nickel, 2.02%-4.74% chromium and 42.22%-46.72% sulfur.

[0037] The following is a specific preparation method example of the nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface.

[0038] Example 1

[0039] This embodiment relates to a method for preparing a nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, referring to Figure 1 As shown, the following steps are included:

[0040] S1. Cut the nickel mesh into 1*1cm 2 The small piece was placed in anhydrous ethanol and hydrochloric acid for cleaning for 15 minutes in turn, and finally placed in distilled water for ultrasonic cleaning for 10 minutes to obtain a pretreated nickel mesh.

[0041] S2. Place 5 mmol of nickel sulfate hexahydrate, 40 mmol of thiourea and 1 mmol of chromium nitrate nonahydrate in a 1 L beaker, add deionized water to 1 L and stir evenly, adjust the pH to 5, and heat to 95° C. to obtain a catalyst electrodeposition precursor solution.

[0042] S3, electrochemical deposition was performed using a three-electrode system. The nickel mesh pretreated in S1 was placed in the catalyst electrodeposition precursor solution as the working electrode, and the platinum sheet was used as the counter electrode at -5 mA / cm 2 The electrode was then washed with deionized water and dried to obtain a nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, wherein the molar percentages of Cr, Ni, and S in the deposited coating were 2.84%, 52.50%, and 44.66%, respectively.

[0043] Example 2

[0044] This embodiment relates to a method for preparing a nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, comprising the following steps:

[0045] S1. Cut the nickel mesh into 1*1cm 2 The small piece was placed in anhydrous ethanol and hydrochloric acid for cleaning for 15 minutes in turn, and finally placed in distilled water for ultrasonic cleaning for 10 minutes to obtain a pretreated nickel mesh.

[0046] S2. Place 5 mmol of nickel sulfate hexahydrate, 40 mmol of thiourea and 0.5 mmol of chromium nitrate nonahydrate in a 1 L beaker, add deionized water to 1 L and stir evenly, adjust the pH to 5, and heat to 95° C. to obtain a catalyst electrodeposition precursor solution.

[0047] S3, electrochemical deposition was performed using a three-electrode system. The nickel mesh pretreated in S1 was placed in the catalyst electrodeposition precursor solution as the working electrode, and the platinum sheet was used as the counter electrode at -5 mA / cm 2 The electrode was then washed with deionized water and dried to obtain a nanocone structure hydrogen evolution electrode with a chromium trisulfide / nickel disulfide interface, wherein the molar percentages of Cr, Ni, and S in the deposited coating were 2.24%, 54.64%, and 43.12%, respectively.

[0048] Example 3

[0049] This embodiment relates to a method for preparing a nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, comprising the following steps:

[0050] S1. Cut the nickel mesh into 1*1cm 2 The small piece was placed in anhydrous ethanol and hydrochloric acid for cleaning for 15 minutes in turn, and finally placed in distilled water for ultrasonic cleaning for 10 minutes to obtain a pretreated nickel mesh.

[0051] S2. Place 5 mmol of nickel sulfate hexahydrate, 40 mmol of thiourea and 2 mmol of chromium nitrate nonahydrate in a 1 L beaker, add deionized water to 1 L and stir evenly, adjust the pH to 5, and heat to 95° C. to obtain a catalyst electrodeposition precursor solution.

[0052] S3, electrochemical deposition was performed using a three-electrode system. The nickel mesh pretreated in S1 was placed in the catalyst electrodeposition precursor solution as the working electrode, and the platinum sheet was used as the counter electrode at -5 mA / cm 2 The electrode was then washed with deionized water and dried to obtain a nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, wherein the molar percentages of Cr, Ni, and S in the deposited coating were 3.64%, 51.56%, and 44.80%, respectively.

[0053] Example 4

[0054] This embodiment relates to a method for preparing a nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, comprising the following steps:

[0055] S1. Cut the nickel mesh into 1*1cm 2The small piece was placed in anhydrous ethanol and hydrochloric acid for cleaning for 15 minutes in turn, and finally placed in distilled water for ultrasonic cleaning for 10 minutes to obtain a pretreated nickel mesh.

[0056] S2. Place 5 mmol of nickel sulfate hexahydrate, 40 mmol of thiourea and 3 mmol of chromium nitrate nonahydrate in a 1 L beaker, add deionized water to 1 L and stir evenly, adjust the pH to 5, and heat to 95° C. to obtain a catalyst electrodeposition precursor solution.

[0057] S3, electrochemical deposition was performed using a three-electrode system. The nickel mesh pretreated in S1 was placed in the catalyst electrodeposition precursor solution as the working electrode, and the platinum sheet was used as the counter electrode at -5 mA / cm 2 The electrode was then washed with deionized water and dried to obtain a nanocone structure hydrogen evolution electrode with a chromium trisulfide / nickel disulfide interface, wherein the molar percentages of Cr, Ni, and S in the deposited coating were 4.54%, 50.39%, and 45.07%, respectively.

[0058] Comparative Example 1

[0059] This comparative example relates to a method for preparing a nickel disulfide electrode, comprising the following steps:

[0060] S1. Cut the nickel mesh into 1*1cm 2 The small piece was placed in anhydrous ethanol and hydrochloric acid for cleaning for 15 minutes in turn, and finally placed in distilled water for ultrasonic cleaning for 10 minutes to obtain a pretreated nickel mesh.

[0061] S2. Place 5 mmol of nickel sulfate hexahydrate and 40 mmol of thiourea in a 1 L beaker, add deionized water to 1 L and stir evenly, adjust the pH to 5, and heat to 95° C. to obtain a catalyst electrodeposition precursor solution.

[0062] S3, electrochemical deposition was performed using a three-electrode system. The nickel mesh pretreated in S1 was placed in the catalyst electrodeposition precursor solution as the working electrode, and the platinum sheet was used as the counter electrode at -5 mA / cm 2 The electrode was then deposited at a current density of 60 min. After the deposition, it was rinsed with deionized water and dried to obtain a nickel disulfide electrode, wherein the molar percentages of Cr, Ni, and S in the deposited coating were 0.00%, 58.08%, and 41.92%, respectively.

[0063] Comparative Example 2

[0064] This comparative example is a Raney nickel electrode. The Raney nickel electrode is an electrode widely used in industrial water electrolysis to produce hydrogen, and the preparation method thereof will not be described in detail.

[0065] Test Example 1

[0066] The nanocone structure hydrogen evolution electrode (denoted as Cr-Ni3S2 electrode) at the interface of chromium trisulfide / nickel disulfide prepared in Example 1 and the nickel disulfide (Ni3S2) electrode prepared in Comparative Example 1 were subjected to scanning electron microscopy (SEM) analysis. Figure 2 As shown, Figure 2 a1 and Figure 2 a2 is the surface morphology of the Ni3S2 electrode prepared in Comparative Example 1, Figure 2 b1 and 2b2 are the surface morphology images of the Cr-Ni3S2 electrode prepared in Example 1. By comparison, it can be seen that the Cr-Ni3S2 catalyst formed after the introduction of the Cr element forms a smaller and more dense micro-cone structure compared to the pure Ni3S2 catalyst, and the scale of the micro-cone changes from 400nm-1μm to 50-200nm. This structural change greatly increases the active area of ​​the catalyst.

[0067] The Cr-Ni3S2 electrode prepared in Example 1 and the Ni3S2 electrode prepared in Comparative Example 1 were analyzed by transmission electron microscopy (TEM). Figure 3 As shown, Figure 3 a1. Figure 3 a2 and Figure 3 a3 is the TEM image of the Ni3S2 electrode prepared in Comparative Example 1, Figure 3 b1. Figure 3 b2 and Figure 3 b3 is a TEM image of the Cr-Ni3S2 electrode prepared in Example 1. Figure 3 a1. Figure 3 a2 and Figure 3 In a3, the (110) and (113) crystal planes of Ni3S2 can be observed, and their lattice spacings are 0.287nm and 0.183nm, indicating that the Ni3S2 catalyst was successfully formed on the nickel mesh. Figure 3 b1. Figure 3 b2 and Figure 3 b3 shows that after the introduction of Cr element, the catalyst forms an interface heterojunction of Ni3S2 and Cr2S3, which are the (110) crystal plane of Ni3S2 with a crystal plane spacing of 0.287nm and the (11-3) crystal plane of Cr2S3 with a crystal plane spacing of 0.261nm. The Ni3S2 / Cr2S3 interface heterojunction formed by these two crystals can effectively improve the electrochemical activity of the catalyst.

[0068] The Cr-Ni3S2 electrode prepared in Example 1 and the Ni3S2 electrode prepared in Comparative Example 1 were subjected to X-ray diffraction analysis (XRD). Figure 4As shown in the figure, by comparison, the half-peak width of the Ni3S2 diffraction peak in the Cr-Ni3S2 electrode is lower than that in the Ni3S2 electrode. This is because the introduction of Cr leads to the formation of more S vacancies in the catalyst, and the formation of such S vacancies can effectively improve the electrochemical activity of the catalyst.

[0069] The Cr-Ni3S2 electrode prepared in Example 1 and the Ni3S2 electrode prepared in Comparative Example 1 were subjected to Raman analysis. Figure 5 As shown, through the comparison of Raman images, it can be seen that the introduction of Cr does reduce the Ni-S bonds in the catalyst, and forms Cr-S bonds, Cr-OH bonds and surface adsorbed water peaks. The formation of this Cr-OH bond can increase the adsorption capacity of the catalyst surface for water and further improve the catalytic performance of water electrolysis.

[0070] The Cr-Ni3S2 electrode prepared in Example 1 and the Ni3S2 electrode prepared in Comparative Example 1 were subjected to X-ray photoelectron spectroscopy (XRS) analysis. Figure 6 As shown, by comparison, it can be found that the Ni in Cr-Ni3S2 catalyst 2+ Compared with the Ni3S2 catalyst, there is a positive shift of 0.1 eV, while S 2- This indicates that electrons were transferred from Ni to S after the introduction of Cr.

[0071] Test Example 2

[0072] The nanocone structure hydrogen evolution electrodes with chromium trisulfide / nickel disulfide interface prepared in Examples 1-4, the nickel disulfide electrode prepared in Comparative Example 1, and the Raney nickel electrode in Comparative Example 2 were subjected to overpotential tests respectively. The specific test methods are as follows:

[0073] At 80°C, linear sweep voltammetry was used with 30 wt% KOH as the electrolyte. The electrodes of the examples and comparative examples were used as working electrodes, 60 mesh pure nickel mesh (1 cm*1 cm) was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The current density-potential curves of the hydrogen evolution electrodes prepared in Examples 1-4 relative to the reversible hydrogen electrode are shown in Table 1. Figure 7 As shown in Example 1, when the doping amount of chromium nitrate reaches 1mmol / L, the catalytic effect of the hydrogen evolution electrode reaches the best (500mA / cm 2 The overpotential under the current density is only 0.253V). In Examples 3 and 4, as the concentration of chromium nitrate increases, the synthesis of Ni3S2 in the catalyst is affected and the catalyst activity decreases; while in Example 2, the concentration of chromium nitrate is too low to form an interface heterojunction between Cr2S3 and Ni3S2, which affects the kinetics of the catalytic reaction.

[0074] Example 1, Comparative Example 1-2 The current density-potential curve of the hydrogen evolution electrode relative to the reversible hydrogen electrode is shown in FIG. Figure 8 As shown in the figure, it can be seen that the nanocone structure hydrogen evolution electrode with chromium trisulfide / nickel disulfide interface in Example 1 reaches 500mA / cm 2 The overpotential under the current density only needs to be 0.253V, which is much lower than the nickel disulfide water electrolysis hydrogen evolution electrode (0.311V) of comparative example 1 and the commercial Raney nickel electrode (0.422V) of comparative example 2. This proves the superiority of the nanocone structure hydrogen evolution electrode with chromium trisulfide / nickel disulfide interface prepared in the embodiment of the present invention.

[0075] In order to further demonstrate the beneficial effects of the present invention, the electrodes obtained in Examples 1-4 and Comparative Example 1 were used as working electrodes, platinum sheets were used as counter electrodes, and Ag / AgCl electrodes were used as reference electrodes. Linear sweep voltammetry was used to measure the relative humidity of the samples at 5 mVs -1 The catalytic performance of hydrogen evolution on water decomposition was tested at a scanning rate of 80°C in a 30wt% KOH aqueous solution. All tests were carried out at room temperature. The measured potential was calculated according to V RHE =V Ag / AgCl +ph×0.059V+0.197V was used for correction, and the final measured result was relative to the standard hydrogen electrode potential. The test results are shown in Table 1. It can be seen that the hydrogen evolution electrodes prepared in Examples 1-4 have excellent catalytic activity, especially the nanocone structure hydrogen evolution electrode with chromium trisulfide / nickel disulfide interface prepared in Example 1 at 500 (mAcm -2 ) corresponds to an overpotential of only 253 mV, while the nickel disulfide electrode prepared in Comparative Example 1 has an overpotential of 500 (mAcm -2 ) corresponds to an overpotential of up to 311 mV, which shows that the nanocone structure hydrogen evolution electrode with chromium trisulfide / nickel disulfide interface of the present invention has a more excellent catalytic activity.

[0076] Table 1

[0077] Example Molar percentage of Cr, Ni, S elements <![CDATA[500(mA cm -2 ) corresponding to the overpotential mV]]> Example 1 Cr 2.84%, Ni 52.50%, S 44.66% 253 Example 2 Cr 2.24%, Ni 54.64%, S 43.12% 268 Example 3 Cr 3.64%, Ni 51.56%, S 44.80% 282 Example 4 Cr 4.54%, Ni 50.39, S 45.07% 296 Comparative Example 1 Cr 0.00%, Ni 58.08%, S 41.92 311

[0078] In summary, the present invention uses a nickel mesh as a conductive substrate, and in-situ grows a nanocone structure coating with a chromium trisulfide / nickel disulfide interface on the nickel mesh as a hydrogen evolution catalyst, wherein the chromium trisulfide / nickel disulfide interface layer has a high water decomposition activity, optimizes the problem of difficult desorption of hydrogen atoms from the nickel disulfide catalytic coating, and introduces more active sites, greatly reduces the overpotential required for water decomposition, and effectively improves the hydrogen evolution efficiency; a one-step electrochemical deposition method is adopted, the preparation method is simple and efficient, the catalyst has strong stability, and the prepared hydrogen evolution electrode has broad application prospects in the field of hydrogen production by alkaline water electrolysis.

[0079] The present invention is described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements can be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The protection scope of the present invention is determined by the attached claims.

Claims

1. A nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, characterized in that: The invention comprises a conductive substrate and a nano-cone structure catalytic coating layer which is in-situ grown on the conductive substrate and has a chromium trisulfide / nickel disulfide interface.

2. The nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface as claimed in claim 1, characterized in that: The thickness of the catalytic coating is 20-45 μm, and the size of the nanocone structure is 50-200 nm.

3. The nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface as claimed in claim 1, characterized in that: In terms of molar percentage, the catalytic coating comprises the following components: 49.57%-55.38% nickel, 2.02%-4.74% chromium and 42.22%-46.72% sulfur.

4. A method for preparing a nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface, characterized in that: The steps include: S1, dissolving a soluble nickel salt, a soluble chromium salt and a soluble sulfur salt in a solvent, adjusting the pH and temperature to obtain a precursor solution; S2. Placing a conductive substrate in the precursor solution for electrochemical deposition, in situ growing a nanocone structure catalytic coating having a chromium trisulfide / nickel disulfide interface, and obtaining the nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface.

5. The nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface as claimed in claim 4, characterized in that: In S1, the soluble nickel salt is selected from one or more of nickel sulfate, nickel chloride and nickel nitrate; the soluble chromium salt is selected from one or more of chromium sulfate, chromium chloride and chromium nitrate; the soluble sulfur salt is selected from thiourea and / or sodium sulfide.

6. The nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface as claimed in claim 4, characterized in that: In S1, the concentration of nickel ions in the precursor solution is 1-5 mmol / L, the concentration of chromium ions is 0.5-3 mmol / L, and the concentration of sulfur ions is 10-40 mmol / L.

7. The nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface as claimed in claim 4, characterized in that: In S1, the pH of the precursor solution is 4-5, and the temperature is 80-95°C.

8. The nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface as claimed in claim 4, characterized in that: In S2, the current density of the electrochemical deposition is -5 to -20 mA / cm 2 , the electrochemical deposition time is 30-90min.

9. The nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface as claimed in claim 4, characterized in that: Before S2, the method further includes: placing the conductive substrate in anhydrous ethanol, hydrochloric acid and distilled water in sequence for cleaning; the conductive substrate is a nickel mesh.

10. Use of the nanocone structure hydrogen evolution electrode having a chromium trisulfide / nickel disulfide interface according to any one of claims 1 to 3 in catalyzing hydrogen evolution reaction in alkaline water electrolysis.

Citation Information

Patent Citations

  • Co9S8 / Ni3S2 compound, redox medium electrode, preparation method of redox medium electrode and modular electrochemical hydrogen production system

    CN117626334A